Development of special cold spray nozzle for internal surface coating deposition - Shorinov, Oleksandr; Volkov, Andrii; Savchenko, Nina; Markovych, Serhii; Danko, Kostiantyn; Ipatov, Roman (Technology audit and production reserves, 2025)
Increasing the service life of parts by forming protective and restorative coatings through cold spraying (CS) is a tough scientific and technical challenge. The object of the study is the process of accelerating powder particles in a supersonic rotating nozzle for CS. For CS, it is difficult, and sometimes even impossible, to form coatings on internal and hard-to-reach surfaces. In the practice of using the technology, this is considered one of the most problematic places, which limits the capabilities of the technology. This paper focused on improving the CS process by developing a new supersonic rotating nozzle for coating deposition on internal and hard-to-reach surfaces of parts, establishing the regularities of the trajectory of motion and acceleration of powder particles in it. During the study, classical methods of computational gas dynamics were used, including methods for investigating two-phase flows. Experimental verification of the modeling results was performed by the pneumatic method of determining the Mach number using a Pitot-Prandtl tube. Numerical modeling of CS processes was performed for two designed rotating nozzles – two-channel and three-channel. The values of the maximum velocity of aluminum powder particles with a diameter of 10 μm at an air stagnation pressure of 4.0 MPa and stagnation temperature of 550°C were obtained: 558 m/s for the two-channel nozzle, and 585 m/s for the three-channel one, which is sufficient for adhesion of particles to the substrate. A three-channel nozzle was chosen for manufacturing and experimental testing. The difference between the experimental and calculated values of the Mach number at the nozzle outlet did not exceed 10%. The presence of two additional nozzles, located in the main channel and directed at an angle to the main flow direction, ensures the rotation of the flow with particles from the initial direction at an angle of approximately 75 degrees, which satisfies the requirements for forming CS coatings.